An Estelle compiler - Van Dijk, Jacques (Department of Computer Science, 2016)
The increasing development and use of computer networks has necessitated international standards to be defined. Central to the standardization efforts is the concept of a Formal Description Technique (FDT) which is used to provide a definition medium for communication protocols and services. This document describes the design and implementation of one of the few existing compilers for the one such FDT, the language "Estelle" ([ISO85], [ISO86], [ISO87]).